Association between Endocan, PAI-1 and intima media thickness in patients with high diabetes risk - Parakhina, V.; Laryushina, Ye.M.; Ponamareva, O. (Fundamental and Experimental Biology, 2022)
There is no information in the literature on the ratio of the concentrations of Endocan, PAI-1, and intima media thickness (IMT) in patients with high diabetes risk. This study aims to investigate the relationships between endothelial dysfunction biomarkers: Endocan, Plasminogen Activator Inhibitor-1(PAI-1), insulin resistance (IR) indicators, and IMT of the common carotid artery (CCA) in patients with risk of type 2 diabetes mellitus (T2DM). A case-control study was held, including 184 individuals, aged from 18 to 65 years. According to FINDRISC scale, patients were divided into 2 groups: Group 1 (n= 138) — low risk of T2DM (<12 points) and Group 2 (n = 46) high risk of T2DM (>12 points). IMT more than 0.9 mm on ultrasound considered as an atherosclerosis. Significant differences were found when studying the level of Endocan, PAI-1 biomarkers with their predominance in the group of patients with a high risk of T2DM; concentrations of Endocan comprised (mean±SD) 1698.2±576.2 pg/ml; p=0.01; PAI-1–32307.15±19947.12 pg/ml; p=0.05 to compare with low risk of T2DM. In addition to, mean values of IMT prevailed in patients in the group with a high diabetes risk and comprised right IMT CCA-0.90±0.15 mm; p = 0.05, left IMT CCA-0.91±0.14 mm; p=0.02. Interrelations between Endocan, PAI-1, and IMT CCA have been determined by correlation analysis. These findings indicate that in patients with high diabetes risk the elevations of the Endocan, PAI-1 is associated with a subclinical atherosclerosis. Furthermore, both biomarkers Endocan and PAI-1 has been demonstrating significant correlation with insulin, IR-HOMA index, С-peptide, HbA1c, and fasting glucose in patients with high risk of T2DM. We found significant relationships between the ED biomarkers with IMT and IR in patients with high risk of T2DM. We suggest that rising of IR leads to Endocan and PAI-1 elevation, subclinical atherosclerosis and thereby increase ED and cardiovascular risk in these patients.